Pyriproxyfen-treated polypropylene sheets and resting boxes for controlling mosquitoes in livestock operations - Pattarapon Khemrattrakool (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Many insect vector species of medical and veterinary importance are found abundantly in areas where animals are held. In these areas, they often rest for a period of time on objects around the animals both before and after blood feeding. However, the use of neurotoxic insecticides for vector control is not advised for use in such shelters as these chemicals can pose hazards to animals. The present study evaluated the efficacy of pyriproxyfen (PPF), an insect growth regulator, applied to polypropylene sheets and resting boxes on the reproductivity of mosquitoes found in animal shelters in Chiang Mai, Thailand. The sheets sprayed with 666 mg PPF/m2 were set on the inner wall of a cowshed and kept in place for 3 h (6.00 to 9.00 pm). During this time, fully blood-fed female mosquitoes that landed and remained continuously on the sheets for 5, 10, and 20 min were collected. The results, involving Anopheles subpictus, An. vagus, Culex gelidus, Cx. tritaeniorhynchus, and Cx. vishnui, revealed significant reductions in oviposition rates, egg hatchability, pupation, and adult emergence in the PPF-treated groups compared to the control groups. Adult emergence rates were reduced to 85.6–94.9% and 95.5–100% in those exposed for 10 and 20 min, respectively. The sheets retained their effectiveness for three months. The PPF-treated (666 mg/m2) resting boxes (35 _ 35 _ 55 cm) were placed overnight at a chicken farm where Cx. quinquefasciatus predominated. Blood-fed mosquitoes were collected in the morning and reared in the laboratory. Oviposition rates were reduced by 71.7% and adult emergence was reduced by 97.8% compared to the controls. PPF residual spray on surface materials in animal sheds is a potential method for controlling mosquitoes. Further studies are needed to evaluate the impact of PPF-treated materials on wild populations.